Morphometric study of the acetabulum roof for optimum implant placement of quadrilateral plate fracture - Jeyasingam, Kuhaendra (2022)
Introduction Acetabular fracture involving quadrilateral plate (QLP) is complicated as the manoeuvre to reduce the fracture is challenging. Improper reduction of QLP fracture will cause significant morbidity to the patient. However, to date, there is no optimum implant to stabilize this fracture safely without compromising the hip joint and no study to measure the standard parameters of acetabulum among the Malaysian population. Thus, this study was conducted to determine the safety profile of the acetabulum for optimum implant placement among Malaysian population. Materials and methods This retrospective study used data from patient’s record and PACS system in Hospital Universiti Sains Malaysia (HUSM). All patients aged 18 years and older were included. Those with bilateral acetabular fracture, prior pelvic instrumentation, congenital pelvic abnormality or pathology and image artefacts were excluded from this study. Materialise Interactive Medical Image Control System (MIMICS) version 21.0 software converted the Digital Imaging and Communication in Medicine (DICOM) data to three-dimension (3D) model. Subsequently, measurement of length and angle of acetabulum roof were made. Statistical Package for the Social Sciences (SPSS) version 26 was used for analysis. A continuous variable was summarized as mean and standard deviation (SD). An independent T-test was run to compare the mean difference between length A-B (pubic tubercle to anterior limit acetabulum), A-D (pubic tubercle to midpoint acetabulum), A-C (pubic tubercle to posterior limit acetabulum) and X-Y angle (safe angle of implant) among gender. Results Fifty-six patients were recruited in this study. The mean patient age was 37 years old, whereby minimum age was 18 years and the maximum age was 86 years. 82.1% were male, and 17.9% were female. All patients were Malay. All measurements were observed to be greater among males. T-test analysis revealed significant mean difference in measurement of acetabulum length and A-C distance between gender. Otherwise, there were no significant mean differences in measurements between A-B, A-D and X-Y angle among gender. Ideal placement of QLP is between 59.24-62.05mm from pubic tubercle and safe plate angle is more than 26.62 degree. Conclusion This study provides sufficient and reproducible knowledge to orthopaedic surgeons regarding normal acetabular anatomy among Malaysian population to facilitate internal fixation of QLP fracture. In addition, measurements obtained from this study can aid in developing a suitable implant design for optimum implant placement. This will eventually reduce complication rates and morbidity to patient.